2020
DOI: 10.1038/s41598-020-67591-5
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of enhanced recovery after surgery program components implemented in laparoscopic appendectomy: prospective randomized clinical study

Abstract: Background Laparoscopic appendectomy (LA) is a widely used surgical procedure. Patients often suffer from considerable postoperative pain and indigestion, which prolongs their in-hospital stay. Almost 10% of patients develop postoperative complications. The enhanced recovery after surgery (ERAS) program has proven its efficacy in elective surgery and could hypothetically improve LA outcomes. Currently, there is no ERAS program for LA. Methods A modified ERAS (mERAS) protocol was studied in a prospective, rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
0
10
0
2
Order By: Relevance
“…A total of 1021 distinctive studies were found, of which 31 studies (between 2003 and 2021) satisfied the inclusion criteria and were comprised in the study 14‐44 . The 32 studies included 4448 subjects with gastrointestinal surgery at the start of the study: 2242 of them were provided with rapid rehabilitation and 2206 were standard care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1021 distinctive studies were found, of which 31 studies (between 2003 and 2021) satisfied the inclusion criteria and were comprised in the study 14‐44 . The 32 studies included 4448 subjects with gastrointestinal surgery at the start of the study: 2242 of them were provided with rapid rehabilitation and 2206 were standard care.…”
Section: Resultsmentioning
confidence: 99%
“…This meta‐analysis study based on 31 studies included 4448 subjects with gastrointestinal surgery at the start of the study: 2242 of them were provided with rapid rehabilitation and 2206 were standard care 14‐44 . Rapid rehabilitation had significantly lower complications and wound infection compared with standard care in subjects with gastrointestinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A periappendicular abscess is a difficult procedure that should be conducted during the day. Most people who have undergone a non-perforated appendix ectomy may go home within 23 hours after the operation (11) . In this study, we compared laparoscopic and open surgery for suspected appendicitis.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated laparoscopic appendectomy for nonperforated appendicitis to be safely performed as fast-track protocols for children [4][5][6] and adults [7]. Recently, randomized controlled trials of laparoscopic appendectomy in appendicitis was conducted [8,9] and the ERAS program for laparoscopic appendectomy has advantages over the traditional approach.…”
Section: Introductionmentioning
confidence: 99%